1994
DOI: 10.1002/tcm.1770140106
|View full text |Cite
|
Sign up to set email alerts
|

Preferential pericentric lesions and aneuploidy induced in mouse oocytes by the topoisomerase II inhibitor etoposide

Abstract: Etoposide (VP-16) is used as an antineoplastic drug in humans. It inhibits topoisomerase II(topoII) activity by forming a ternary complex (DNA-etoposide-topoII). This complex prevents the DNA-strand rejoining activity of topo II, which results in DNA-strand breaks and the formation of structural chromosome aberrations. Topo II activity is also required for removing regions of DNA catenation prior to chromosome segregation. The possibility exists that patients undergoing etoposide chemotherapy may incur genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 26 publications
5
20
0
Order By: Relevance
“…The frequency of hyperhaploidy found in MII spermatocytes after treatment of pachytene spermatocytes is the highest ever reported for an aneugen in male germ cells (41,42). Also, unlike model aneugens, such as colchicine and vinblastine, for which male germ cells seem to be less sensitive than female germ cells (47), the frequency of hyperhaploidy found in MII spermatocytes in this study was similar to that found in MII oocytes (20).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The frequency of hyperhaploidy found in MII spermatocytes after treatment of pachytene spermatocytes is the highest ever reported for an aneugen in male germ cells (41,42). Also, unlike model aneugens, such as colchicine and vinblastine, for which male germ cells seem to be less sensitive than female germ cells (47), the frequency of hyperhaploidy found in MII spermatocytes in this study was similar to that found in MII oocytes (20).…”
Section: Discussionsupporting
confidence: 84%
“…It has been reported that exposure of germ cells to ET results in a preferential localization of the aberrations near the centromere (20,23,24). We have observed a similar phenomenon in both MI and MII spermatocytes.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Therefore, topoisomerase II interactive agents have potential clastogenic and aneugenic actions on meiotic cells. Etoposide, a specific topoisomerase II inhibitor, caused both structural chromosome aberrations and aneuploidy in primary oocytes of the mouse [3,4] and the Chinese hamster [5]. Similar chromosomal effects of the inhibitor were found in mouse primary spermatocytes [6,7].…”
Section: Introductionmentioning
confidence: 66%
“…Past studies hinted at the possibility of a limited DDR in fully grown oocytes (Mailhes et al, 1994;Bradshaw et al, 1995). More specifically, it has been shown that a significant delay in the duration of MI is not observed following injection into female mice of etoposide, a topoisomerase II inhibitor and DSB inducer (Mailhes et al, 1994;Bradshaw et al, 1995).…”
Section: Prophase To MI Transitionmentioning
confidence: 99%